Pembentukan Karakter Positif pada Remaja melalui Sosialisasi Pencegahan Bullying di SMP Dharma Utama Sukasari - Arivia Raihanah Lubis; Nadlrah Naimi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Bullying is an act of violence against individuals both verbally and non-verbally that results in traumatized individuals to carry out activities in general. In recent months, there has been a lot of news that there is child violence committed by their own friends, parents and the community. Both in the educational environment and in the community, for this reason, it is necessary to make joint commitments to make efforts to prevent acts of verbal and non-verbal violence both through social media directly and with other tools. It is due to the lack of understanding of the dangers of bullying for it is very interesting if this is solved. This commitment is not enough only from education but must cooperate with various parties, both authorities, the community, guardians, students, and community leaders. The method in socialization of the prevention of violence against children (bullying) has several stages in the first stages of planning, organizing, implementing socialization, mentoring and evaluation. The main target that is expected in the implementation of this activity is so that the public knows the rules of the law on child violence and also the psychological danger for children who experience such violence. The results of this activity were immediately felt because many communities, students and education directly provided input to carry out continuous assistance and immediately obtained positive results with an understanding of the dangers of bullying for children affected by bullying both psychologically and non-psychologically.